Agglomeration behavior of the dense medium in a gas–solid separation fluidized bed. (1st May 2023) - Zhang, Yadong; Dong, Yani; Lv, Guannan; Dong, Liang; Zhao, Yuemin; Duan, Chenlong; Zhou, Enhui; Hua, Wei
Graphical abstract: Highlights: The mechanism of particle adhesion clusters in gas solid fluidized bed was quantitatively investigated. The competitive effect of different micro-forces between adherent particles was studied. The effect of different operating factors on particle agglomeration was studied. Abstract: In this study, the atomic force microscopy (AFM) was used to measure the micro-forces between different particles and study the influence of different operating parameters on the formation of particle clusters in the gas–solid fluidized bed separation process. In this way, the mechanism of liquid bridge formation and fracture can be elucidated, thereby providing a theoretical basis for inhibiting the formation of particle clusters. The results indicated that for relative humidity (RH) < 40%, the extrusion liquid bridge is the dominant factor for the formation of the particle liquid bridge, and the liquid film thickness, h, and liquid film volume, V sq, vary linearly with RH; however, once the RH is > 40%, these relationships become nonlinear. The adhesion force between magnetite powder particles was found to be the largest and that between pulverized coal particles was found to be the smallest, with the mixture of the two particle types being in between. Further, the adhesion between particles increased monotonically with RH, while showing a maximum value with increasing particle separation. A theoretical analysis of the critical fracture distance, D rupture *, of the particle liquid bridge showed that, as the liquid bridge volume, V *, and contact angle, θ, increase, D rupture * gradually increases, but its rate of increase rate. The theoretical analysis was found to be largely consistent with the experimental data, only deviating at low RH.